Hubungan Antara Menulis Huruf Tegak Bersambung pada Kemampuan Membaca Siswa Sekolah Dasar - Putri, Aisah Diana; Rigianti, Henry Aditia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this digital era that is sophisticated and easy, writing by hand especially cursive writing becomes one of the topics of discussion why it is still learned in this era. Whereas cursive writing has many benefits for students. The purpose of this literature review is to provide an overview of the relationship between cursive writing and the reading ability of elementary school students. The method used in this study is the literature study or literature review method. The technique used is collecting, analyzing, and summarizing information related to the research topic. Based on the literature review conducted, cursive writing skills have many benefits including training visual-motor skills, visual spatial skills, spelling, cognitive skills, and understanding of writing so that students’ reading skills become better and faster to capture the content of the reading. Another result of this study is that cursive writing activates the synaptic network of students’ brains so that the information read by students can be remembered longer and also through this cursive writing activity students’ patience is also well honed. Therefore, cursive writing can be one of the strategies to improve students’ reading skills. Keywords: Writing, Reading, Cursive Writing.